2009
DOI: 10.1111/j.1747-5457.2009.00446.x
|View full text |Cite
|
Sign up to set email alerts
|

Facies Analysis and Depositional Sequences of the Upper Jurassic Mozduran Formation, a Carbonate Reservoir in the Kopet Dagh Basin, Ne Iran

Abstract: Upper Jurassic carbonates of the Mozduran Formation constitute the principal reservoir intervals at the giant Khangiran and Gonbadli gasfields in the Kopet Dagh Basin, NE Iran. These carbonates were investigated using detailed field studies and petrographic and wireline log analyses in order to clarify their depositional facies and sequence stratigraphy. Facies were interpreted to reflect deep basin, fore-shoal, shelf margin, lagoon, tidal flat and coastal plain depositional systems.The Mozduran Formation is c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 60 publications
1
34
0
Order By: Relevance
“…The presence of burrows without sediment filling supports their development in consolidated sediments. The evidence of their intense bioturbation reflects low/break in sedimentation rate according to Kavoosi et al (2009), moderate sediment supply rate is also reported by Odumoso et al (2013) and this is indicative of sediments of foreshore/shoreface environments. The presence of wavy laminations with relatively high feldspar content supports sediments deposition under turbulence in a continental shelf environment.…”
Section: Faciessupporting
confidence: 52%
See 1 more Smart Citation
“…The presence of burrows without sediment filling supports their development in consolidated sediments. The evidence of their intense bioturbation reflects low/break in sedimentation rate according to Kavoosi et al (2009), moderate sediment supply rate is also reported by Odumoso et al (2013) and this is indicative of sediments of foreshore/shoreface environments. The presence of wavy laminations with relatively high feldspar content supports sediments deposition under turbulence in a continental shelf environment.…”
Section: Faciessupporting
confidence: 52%
“…The interpretation of facies can be by considering the depositional environments, processes and the prevailing conditions at the time of deposition. Different energy levels of the depositional media could reflect variable sedimentary facies as the sedimentary structures will be different with a possible similar composition of the sediments, hence, the grouping of the sediments into facies is principally based on the observed sedimentary structures, which reflects the depositional environments, conditions and processes, the composition and the texture of the sediments (Tucker, 2004;Kavoosi et al, 2009).…”
Section: Sedimentary Faciesmentioning
confidence: 99%
“…In both cases they were characterized as shallow marine sediments deposited above fair-weather wave base. Also, Kavoosi et al (2009) interpreted the same microfacies association from Upper Jurassic rocks of NE Iran as fore-shoal deposits. The non-fossiliferous calcimudstones forming uppermost levels of the Porto Koufos Limestones (interval IV, Fig.…”
Section: Depositional Environmentmentioning
confidence: 92%
“…Hereafter, the Amu-Darya Basin entered the development stage of rift basin [63] and a period of stable settlement. In Lower-Middle Jurassic, there were the clastic sediments with greater thickness [64], which were unconformably contacted with the underlying stratum [65]. In Middle Jurassic Bathonian Stage/Callovian Stage, there was large-scale transgression, and the successive paleo-uplifts (e.g., Chardzhou, Dengizkul, Sandykly) and basement faults in the basin controlled the deposition of …”
Section: Sedimentary-sequence Evolution Characteristics Of Callovian-mentioning
confidence: 99%